Open Source Archaeology : Ethics and Practice - Andrew T. Wilson; Ben Edwards (De Gruyter Open Poland, 2015)
Open Source Archaeology: Ethics and Practice'brings together authors and researchers in the field of open-source archaeology, defined as encompassing the ethical imperative for open public access to the results of publicly-funded research; practical solutions to open-data projects; open-source software applications in archaeology; public information sharing projects in archaeology; open-GIS; and the open-context system of data management and sharing. This edited volume is designed to discuss important issues around open access to data and software in academic and commercial archaeology, as well as to summarise both the current state of theoretical engagement, and technological development in the field of open-archaeology. Ben EdwardsBen Edwards was trained in archaeology at the University of Durham, achieving his BA, MA and PhD. His first commercial work was for Archaeological Services, Durham University, before moving on to become a Lecturer in Archaeological Practice at the University of Liverpool, where he taught for three years. During this time Ben began his project management work, undertaking both commercial and research excavations, and survey projects. His teaching (archaeological practice and heritage management) proved to be an excellent basis from which to develop his professional expertise.Ben now lectures at Manchester Metropolitan University in Archaeology and Heritage. He currently researches open source software and hardware for use in the field, and advanced 3D surveying techniques. Andrew WilsonAndrew Wilson was trained in archaeology at the University of Liverpool. Upon achieving his BA at the University, Andrew moved south to study Computer Applied Archaeology at the University of Southampton, where he was awarded an MSc. Andrew returned to the University of Liverpool where he has recently completed a PhD. During this time Andrew coordinated a number of projects both in the UK and Middle East, specialising in advanced surveying techniques of archaeological remains.Working in the the School of Computer Science, Bangor University Andrew has developed his keen interest in Open data policies and ethics. This interest was the starting point for this volume.